A Solid Redox Mediator Analog as a Highly Efficient Catalyst for Na–O2 Batteries - Shen, Qin-yin; Ma, Jin-ling; Li, Ming-lu; He, Wei; Tan, Ying-yue; Zhou, Peng-yu; Wang, Yu (Batteries (Basel), 2022)
During the discharge of Na–O2 batteries, O2 is reduced and combines with Na+ to form an insulating solid sodium oxide on the cathode, which severely hinders the mass transfer path, resulting in high polarization voltage, low energy efficiency, and short battery life. Hereby, we proposed a novel illumination-assisted Na–O2 battery in which bismuth vanadate (BiVO4) with few defects and high surface areas was used as the catalyst. It showed that the charge overpotential under photo assistance reduced by 1.11 V compared with that of the dark state one. Additionally, the insolating sodium oxide discharge products were completely decomposed, which was the key to running Na–O2 batteries over 200 cycles with a charge potential of no more than 3.65 V, while its counterpart (under dark condition) at 200 cycles had the charge potential higher than 4.25 V. The experiment combined with theoretical calculation shows that few defects, high surface areas, the altered electron transfer kinetics, and the low energy gap and low oxygen absorption energy of the (040) crystal face of monoclinic BiVO4 play an important role in catalyzing oxygen reduction reaction (ORR) and oxygen evolution reaction (OER).